(untitled) (Our Nature, 2009)
Known as "Simsar" in Nepal, wetlands are those areas which lie between the land and deepwater and remian waterlogged or submerged under water, seasonally or throughout the year. Generally the land is so muddy that one cannot easily walk over it, and water is so deep that one can neither swim nor get drowned. River floodplains, shallow margins of lakes and reservoirs, shallow and seasonal ponds, islands in rivers, deepwater paddy fields, and sea-coasts are typical examples of wetlands. Keywords: Lowland wetland, Nepal doi: 10.3126/on.v6i1.1657 Our Nature (2008)6:67-77